Economic Evaluation of Exercise Interventions with a Physiological Approach: Enhancing Health and Reducing Healthcare Costs - Hormati Oughoulbaig, zahra; Mortazavi Blous, Hadi (International Journal of Business Management and Entrepreneurship, 2025)
Introduction and purpose: Global healthcare systems are struggling under the weight of chronic diseases and soaring costs. This has sparked a crucial shift from a focus solely on treatment to a more proactive strategy centered on prevention. Physiologically grounded exercise interventions programs scientifically designed to improve specific bodily functions have emerged as a powerful tool in this new paradigm, promising not only better health but also potential economic benefits. This article aimed to synthesize and compare high-quality economic evidence to determine if these targeted exercise programs offer good value for money across different health conditions. Methods: We conducted a systematic review of economic evaluations published between 2010 and 2025. We analyzed studies that used established economic metrics, such as cost-effectiveness ratios and quality-adjusted life years (QALYs), to assess interventions for conditions like diabetes, heart disease, and musculoskeletal pain. The studies included clinical trials, simulation models, and systematic reviews. Results: The evidence is compelling and consistent. Structured exercise programs were repeatedly found to be a cost-effective or even cost-saving investment. They led to significant health improvements including gains in longevity, mobility, and mental health—while keeping costs manageable for healthcare systems. This held true across various conditions, from cardiac rehabilitation to managing knee osteoarthritis and childhood obesity. Conclusion: The findings make a strong case for reimagining exercise as a core medical prescription rather than a mere lifestyle suggestion. Integrating scientifically-designed exercise programs into standard healthcare is not just an economic imperative but a fundamental step towards building a more sustainable and effective health system that helps people live longer, healthier lives.